x^2 - 3 = - 2x Bring - 2x over to the left.
x^2 + 2x - 3 = 0
You need 2 numbers that multiply to - 3 and add to 2
3 and - 1 are the numbers you need.
(x + 3)(x - 1) = 0
This means that either
x + 3 = 0 in which case
x = -3
or
x - 1 = 0 in which case
x = 1
Just pick the answer that suits this. There is another way. It is much less mathematical. You could simply take all the answers and put them in the quadratic
x^2 + 2x - 3 = 0 Try putting 0 in this.
0*0 + 2*0 - 3 = 0
-3 = 0 That's not correct. So you have eliminated that possible answer.